Holographic Wilson Loops in the Confining Backgrounds at Zero Temperature - Golubtsova, Anastasia A.; Vu, Nguyen Hoang (Communications in Physics, 2019)
We study Wilson loops in the exact renormalization group ow at zero tempera- ture via the 5d holographic model that reproduces the behavior of the QCD running coupling. Calculating the time-like rectangular Wilson loop we show that the model includes a conning phase at T = 0 in the IR region.